Sensitization of trigeminal brainstem pathways in a model for tear deficient dry eye. Issue 5 (May 2015) - Rahman, Mostafeezur; Okamoto, Keiichiro; Thompson, Randall; Katagiri, Ayano; Bereiter, David A.
Abstract : Abstract: Chronic dry eye disease (DE) is associated with an unstable tear film and symptoms of ocular discomfort. The characteristics of symptoms suggest a key role for central neural processing; however, little is known about central neuroplasticity and DE. We used a model for tear deficient DE and assessed effects on eye blink behavior, orbicularis oculi muscle activity (OOemg), and trigeminal brainstem neural activity in male rats. Ocular-responsive neurons were recorded at the interpolaris/caudalis transition (Vi/Vc) and Vc/upper cervical cord (Vc/C1) regions under isoflurane, whereas OOemg activity was recorded under urethane. Spontaneous tear volume was reduced by ∼50% at 14 days after exorbital gland removal. Hypertonic saline–evoked eye blink behavior in awake rats was enhanced throughout the 14 days after surgery. Saline-evoked neural activity at the Vi/Vc transition and in superficial and deep laminae at the Vc/C1 region was greatly enhanced in DE rats. Neurons from DE rats classified as wide dynamic range displayed enlarged convergent periorbital receptive fields consistent with central sensitization. Saline-evoked OOemg activity was markedly enhanced in DE rats compared with controls. Synaptic blockade at the Vi/Vc transition or the Vc/C1 region greatly reduced hypertonic saline–evoked OOemg activity in DE and sham rats. These results indicated that persistent tear deficiency caused sensitization of ocular-responsive neurons at multiple regions of the caudal trigeminal brainstem and enhanced OOemg activity. Central sensitization of ocular-related brainstem circuits is a significant factor in DE and likely contributes to the apparent weak correlation between peripheral signs of tear dysfunction and symptoms of irritation. Abstract : Persistent tear deficiency was sufficient to cause sensitization of neurons at multiple regions of the trigeminal brainstem and enhanced orbicularis oculi muscle activity.